EP262 Primary conization overcomes the risk of local recurrence following laparoscopic radical hysterectomy in early-stage cervical cancer. (1st November 2019) - Bogani, G; Ditto, A; Chiappa, V; Raspagliesi, F
Abstract : Introduction/Background: Accumulating data highlighted that minimally invasive surgery has been associated with higher recurrence rates and worse overall survival than the open approach in women with early-stage cervical cancer. Tumor spread at the time of colpotomy might be advocate as the reason of tumor cells dissemination in the pelvic area. Here, we aimed to investigate if primary conization might overcome the risk of local dissemination in early-stage cervical cancer undergoing laparoscopic radical hysterectomy. Methodology: Consecutive data of 262 early stage cervical cancer patients were retrieved: 88 women had conization followed by radical hysterectomy. A propensity-matched comparison (1:1) was carried out in order to compare laparoscopy and open surgery, minimizing possible selection biases. Results: Data of 35 patients' pair (total 70 patients) were analyzed. No between-group differences in baseline, disease and pathological variables were observed (p>0.20). Patients undergoing laparoscopy experienced a slightly non-significant longer operative time than patients undergoing open surgery (210.8 (±47.7) vs. 187.9 (±24.7) minutes; p=0.089); while laparoscopic approach correlated whit lower blood loss (50 (range, 30–100) vs. 150 (range, 50–500) ml; p<0.001) and shorter length of stay (3 (±0.8) vs. 5.4 (±1.4) days; p<0.001) in comparison to open surgery. Morbidity rate was similar between groups (p=1.00). One local recurrence was observed per group (p=1.00). Type of surgical approach did not influence site of recurrence (p=1.00) as well as survival outcomes, in term of 10-year disease-free (p=0.549, log-rank test) and overall survivals (p=0.615, log-rank test). Conclusion: Our data seems underline that primary conization might overcome the risk of local recurrence following laparoscopic radical hysterectomy in early-stage cervical cancer. Further prospective evidence is needed. Disclosure: Nothing to disclose.